Hypoxia in the intestine or solid tumors: A beneficial or deleterious alarm signal?. Issue 9 (4th September 2014) - Shehade, Hussein; Oldenhove, Guillaume; Moser, Muriel
<x xml:space="preserve">Abstract</x> The transcription factor hypoxia inducible factors (HIF)‐1 functions as a master regulator of oxygen homeostasis. There is increasing evidence that HIF has an essential role to prevent tissue damage in physiological and pathological situations in which cells are deprived of O2. Here, we review the effects of decreased oxygen supply on the innate and adaptive immune responses in the gut and in solid tumors in which the oxygenation profile correlates with the grade of inflammation. Data in the literature indicate that some tumors may co‐opt immune mechanisms induced by HIF‐1 to promote their survival and proliferation. By contrast, HIF‐1 stabilization would have a beneficial effect in the intestinal tract as it would dampen inflammation and promote its resolution. Therefore, stabilization of HIF‐1 in hypoxia may have opposite effects on the integrity of the host, depending on the tissue microenvironment.